O ensino de Física Contemporânea : compreendendo a estrutura do átomo - Arraes, Cacia Simone (2019)
In the 21st century, information reaches students in a matter of seconds, enabling the accumulation of a large amount of information to which learners have access, which certainly affects their interest and curiosity in science. This requires a differentiated attitude from the teacher in order to awaken students for teaching and learning. Aiming at a significant learning that awakens the student to the teaching of Contemporary Physics, this work shows the application of an educational product focused on the teaching of atomic models, which makes use of active methodologies, based on David's learning theory. Ausubel This research shows the details and development of the work done with the first year high school students of the João Matheus Barbosa State School, Juscimeira - MT, which is located 150 km from the capital Cuiabá. The proposal brings the teaching of atomic models through the recording of videos by the students' own cell phones. Aiming to demonstrate that one can teach Modern and Contemporary Physics from the first year of high school, we chose to teach the history of atomic models giving greater emphasis to the current atomic model, which conceives of the electrosphere as an electronic cloud. Providing students with the opportunity to show their creativity and be builders of their knowledge, the work observed the direct participation of students in the debates, their difficulties in relation to the concepts that involved the current atomic model, and may notice a different interest from them during the entire development of the project, highlighting the possibility of approaching Contemporary Physics from the first year of high school, through the concepts of atomic models, thus awakening the students to the technological advances achieved through physics studies, carried out by large scientists who sought answers to the unknown.